Pengembangan Aplikasi Online Store Penyewaan Alat Camping Berbasis Progressive Web App (PWA) Menggunakan Framework Laravel - Suryawan, Mohamad Arif; Ilyas, Ilyas (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
Limited access to real-time information regarding the availability of camping equipment is one of the main obstacles for prospective renters in the rental process. In addition, conventional rental systems tend to be inefficient, provide incomplete information on available equipment, and lack digital features that support integrated booking and rental data management. This study aims to design and develop an online store application for camping equipment rental based on Progressive Web App (PWA) technology using the Laravel framework at Buton Adventure Store Baubau. The system development method employed is the System Development Life Cycle (SDLC) with a V-Model approach, which emphasizes a strong relationship between each design and testing phase to ensure system quality. The application was developed using the Laravel framework to support efficient development, system security, and ease of maintenance. The results show that the developed web-based application can present comprehensive camping equipment information, provide availability checking, online booking, and payment features, and offer a responsive and consistent user interface across multiple devices. Furthermore, the implementation of PWA technology allows the application to remain accessible under unstable network conditions. Overall, the developed application is expected to improve the efficiency of the camping equipment rental process, enhance access to real-time availability information, and deliver a faster, more practical, and modern user experience.